FIRST RECORD OF Amblyomma ovale PARASITIZING HUMAN IN CENTRAL RIO GRANDE DO SUL, BRAZIL - Somavilla Lignon, Julia; Moscarelli Pinto, Diego; Conrad Bohm, Bianca; Gonzalez Monteiro, Silvia (Revista de Ciência Veterinária e Saúde Pública, 2024)
Ticks are one of the most important groups of infectious disease vectors for animals and humans, being responsible for the transmission of pathogens such as bacteria and protozoa, in addition to causing injuries to their hosts during hematophagy. However, there are few cases of parasitism by these ticks in humans in Brazil. Therefore, the objective was to report for the first time the parasitism by Amblyomma ovale (Koch, 1844) in humans in the central region of Rio Grande do Sul, Brazil, in order to alert the population about the risk of infection by pathogens including zoonoses. Therefore, a specimen of ectoparasite found in a woman residing in the city of Santa Maria, Rio Grande do Sul, was sent to the Laboratory of Veterinary Parasitology of the Federal University of Santa Maria for taxonomic identification at the species level. The tick was taxonomically classified as an adult male of A. ovale, concluding that the vector is present in the studied locality and can parasitize humans.